PERAN KUALITAS KEHIDUPAN KERJA DAN KEPRIBADIAN DALAM UPAYA MENINGKATKAN KINERJA DOKTER MELALUI KEPUASAN KERJA (Studi Pada Rumah Sakit Islam Sultan Agung Semarang) - Muhammad Nasir, 124202.0098 (Jurnal Mahasiswa Pasca Sarjana, 2015)
This study aimed to analyze the influence of the quality of work life and personality of the doctors performance with the mediation of job satisfaction in the Hospital Sultan Agung Semarang. The method in this study is the method by the population census taken of 113 respondents. The test used is a test instrument, penguian models and hypothesis testing. Criteria for test instruments KMO value> 0.5, and Loding factor> 0.4 and 0.7 while the Cronbach alpha for the test model using Adjusted R2 and F Test (Goodness of Fit). Hypothesis test in this study used regression analysis using the t test, hypothesis testing is used t test frequency distribution at the level of significance (Î±) 5%., While the mediation test using path analysis test. Based on the results of the study can be summarized as follows: The quality of working life and a significant positive effect on job satisfaction, personality positive and significant impact on job satisfaction, Quality of Work Life positive and significant effect on performance. Personality positive and significant effect on performance. Job satisfaction and significant positive effect on performance. Job satisfaction does not mediate the effect on the performance quality of work life. Job satisfaction mediates the influence of personality on performance. Keywords: Quality of Work Life, Personality, Performance, Job Satisfaction